2019
DOI: 10.1111/obr.12837
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic surgery for the treatment of type 2 diabetes in patients with BMI lower than 35 kg/m2: Why caution is still needed

Abstract: Summary Bariatric surgery has shifted from being a risky procedure to an evidence‐based one, with proven benefits on all‐cause mortality, cardiovascular disease, cancer, and diabetes control. The procedure has an overall positive result on type 2 diabetes mellitus (T2DM), with a substantial number of patients achieving disease remission. This has resulted in several studies assessing possible weight‐independent effects of bariatric surgery on glycemic improvement, in addition to recommendation of the procedure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 153 publications
(472 reference statements)
0
19
0
Order By: Relevance
“…Many of these criteria are associated with worse glycemic outcomes in the long term (higher HbA1c, longer diabetes duration, and insulin use, for example) [17]. Very limited data regarding long-term reduced micro-and macrovascular risk exist in those patients with a longer diabetes duration.…”
Section: Dss-ii Statements and Recommendations Are Only Partially Evimentioning
confidence: 99%
See 2 more Smart Citations
“…Many of these criteria are associated with worse glycemic outcomes in the long term (higher HbA1c, longer diabetes duration, and insulin use, for example) [17]. Very limited data regarding long-term reduced micro-and macrovascular risk exist in those patients with a longer diabetes duration.…”
Section: Dss-ii Statements and Recommendations Are Only Partially Evimentioning
confidence: 99%
“…In the body of the text, there is a mention that surgery may be considered for those patients between 30 and 35 kg/m 2 , in the same situation. In this guideline, differently from the DSS-II, the indication for class I obesity does not rely on glycemic control itself, but on weight loss and comorbidities, which seems more in line with the evidence [17]. Even so, diabetes duration, probably the most important factor regarding glycemic benefits, was omitted once again.…”
Section: Unifying Guidelinesmentioning
confidence: 99%
See 1 more Smart Citation
“…Although many good-quality observational data suggest that cardiovascular disease risk and mortality are reduced after bariatric and metabolic surgery, the number of patients evaluated that already had cardiovascular disease is very small, and even smaller if we consider those with type 2 diabetes. 2 In the large Swedish Obese Subjects study, although similar benefits were suggested, only 1·5% of patients had a history of cardiovascular disease, and only 21 patients with cardiovascular disease were submitted to surgery. 3 …”
mentioning
confidence: 96%
“… 1 We congratulate the authors for bringing up this important discussion, since difficulties around future care of obesity and type 2 diabetes might be a major problem within this context.We would like to point out, however, our disagreement with the algorithm for prioritisation for bariatric and metabolic surgery in patients with type 2 diabetes. Many diabetes characteristics the authors suggest be prioritised are associated with reduced long-term benefits (which we previously discussed in a review 2 ), but we would like to focus on one point here: established cardiovascular disease. This suggestion goes against current evidence.…”
mentioning
confidence: 99%